Europium Fluorescence to Visualize N-Butyl 2-Cyanoacrylate in Embolized Vessels of an Arteriovenous Malformation Swine Model - Calvo, William J. (AJNR Am J Neuroradiol, 2001)
BACKGROUND AND PURPOSE: Standard tissue staining using the lipid dye Oil-Red-O has been previously applied to stain vessel specimens, which were embolized with a mixture of n-butyl 2-cyanoacrylate (NBCA) and oil (Lipiodol). That technique, however, results in nonspecific and nonquantitative staining that does not provide the necessary differentiation between NBCA and Lipiodol. We present an innovative staining procedure that quantifies NBCA within treated tissues. METHODS: An arteriovenous malformation (AVM) model in swine was used to evaluate the polymerization characteristics of various ratios of Lipiodol/NBCA/glacial acetic acid (GAA) mixtures. To determine the depth of NBCA penetration within the AVM model and to characterize the polymerization patterns of various mixtures within the vessel, histologic cross- and longitudinal sections were prepared for microscopy. These paraffin-embedded tissue sections were stained with a europium aryl-β-diketone complex (TEC) to improve differentiation between NBCA and Lipiodol. Quantification of NBCA and Lipiodol within the lumen of rete cross-sections was accomplished using image analysis software to determine percent luminal area occluded by embolization. RESULTS: Upon application of TEC, intense europium fluorescence was seen when the tissue samples were excited by low-power UV light (excitation at 365 nm; emission at 614 nm). The area of europium intensity within the lumen corresponded to NBCA concentration, and addition of GAA aided the NBCA distribution throughout the lumen without affecting fluorescence intensity. It was seen that NBCA could be easily differentiated from Lipiodol and that quantification could be readily performed on these sections because of the improved differentiation. For the case of a 50:50 (vol. %) mixture with an added 20 μL of GAA, luminal area distribution of Lipiodol, NBCA, and blood products was 42.6 ± 3.5%, 33.8 ± 5.7%, and 23.7 ±2.7%, respectively. CONCLUSION: The rare earth metal europium, when added as a fluorescent chelate compound to histologic tissue sections, allowed for differentiation between NBCA and Lipiodol with good detail. These results have facilitated further characterization of NBCA polymerization for the use of AVM embolization.